Ratio and Proportion Learning in the Context of Zakat to Enhance Students' Mathematical Understanding - Eko Yandi Raharjo; Mega Ulandari; Faiqatul Faidah Salsabila; Ainun Nuriana; Arina Manasikana (Journal of Science and Research, 2026)
Mathematics is a discipline that trains students to think critically and reason logically when drawing conclusions about a problem. This is evident in mathematics education, which plays a crucial role—particularly in the use of ratios, percentages, and social arithmetic as tools in various aspects of human life. Understanding the concepts of comparison and proportion is vital in today’s mathematics education, as they relate to the application of ratios and percentages in various real-life situations. The concepts of ratios and proportions help students understand quantitative relationships between quantities and support their mathematical problem-solving skills. However, in practice, many students still struggle to understand the relationships between ratios, percentages, and their application in real-world contexts. One such context that can be used to integrate these concepts is the calculation of zakat using a specific percentage of assets that have reached the nisab threshold. Therefore, this study aims to develop a mathematics learning model by integrating the application of comparison and proportion concepts into zakat calculations through the use of ratios, percentages, and social arithmetic. This study employs a descriptive approach by integrating mathematical concepts into the context of Islamic economics through the resolution of contextual problems related to the nisab and zakat percentage. The results of the study indicate that applying the concepts of ratios and proportions through the context of calculating zakat not only enhances students’ understanding of ratios but also encourages them to be more active and skilled in solving everyday mathematical problems. Such a contextual approach supports more meaningful mathematics learning, as recommended in the mathematics learning standards.